Mozaik BUMDES Waste Bank Application Development Using Android-Based GPS - Sri Wahyuni; hermansyah; Mesra B (Jurnal Mantik, 2022)
In this study, GPS technology was used to determine the location for picking up residents' gar-bage. Previously, a Website-based Garbage Bank application was built which was used as a waste bank transaction information system, waste price information, and citizen savings book information. However, during the implementation of the Website-based Garbage Bank in Pematang Serai Village, there were problems, namely the lack of waste bank volunteers who run the Garbage Bank, especially in picking up waste from residents' homes. The lack of gar-bage collection volunteers results in the accumulation of garbage in the community due to time constraints for customers to deliver their waste to the Waste Bank. So the use of geotagging technology on the Global Positioning System (GPS) can make it easier for the public to report the points where garbage is collected that the garbage officers did not know beforehand so that the garbage collectors can easily find the point of the garbage pick-up location. So the old sys-tem was developed into a Garbage Bank Application using GPS as a Web-site based waste collection and reporting system. With the marking of locations and transportation of waste, it is hoped that there will be active communication between the community and cleaners so that piles of garbage at points that were previously difficult to reach can be handled more quickly. Minimizing the accumulation of waste in the homes of residents who are customers of the Mozaik Waste Bank to create a beautiful, clean and waste-free environment.